ANALYSIS OF COMMUNITY SATISFACTION INDEX (IKM) FOR GOVERNMENT PUBLIC SERVICES IN CIJAWURA - BANDUNG - Sriharyati, Santy; Rachmawati, Tanti; Lismiati, Yati; Armi, Surya; Setiawan, Awan (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2025)
This study aims to evaluate the quality of public facilities and services periodically using the Public Satisfaction Index (IKM) as an assessment instrument. The evaluation refers to the Regulation of the Minister of Administrative and Bureaucratic Reform (PAN/RB) of the Republic of Indonesia Number 14 of 2017 on the Framework for Conducting Public Service Satisfaction Surveys. A quantitative approach was employed, with samples selected randomly. The survey results in Cijawura Subdistrict indicate that the expected conversion interval score reached 84.35 (Very Good category), while the actual score obtained was 80.16 (Good category), resulting in a gap of 4.19. Further analysis of the indicators shows that the average expectation score was 25.46, whereas the actual condition scored 24.19, creating a gap of 1.26. These findings suggest that public services in Cijawura Subdistrict are approaching community expectations. However, aspects such as Service Schedule Certainty still require improvement to enhance service quality and better meet public expectations.